European Week of Local Democracy - Шуст, Наталія Борисівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article analyzes the new political initiative of Local and Regional Authorities of Europe and the European Committee for Regional Democracy - European Week of Local Democracy and its place in Ukraine.